DILEMA INDONESIA ANTARA INDUSTRI ROKOK DALAM NEGERI DAN KERANGKA KERJA WORLD HEALTH ORGANIZATION – FRAMEWORK CONVENTION ON TOBACCO CONTROL - Zidny Ima Hasan; Muhammad Izma Imansyah (Gapenas Publisher, 2023)
This research was motivated by Indonesia's attitude that refused to ratify the FCTC framework, besides that Indonesia's position was listed as the only country that had not ratified the WHO-FCTC framework out of 38 countries in Southeast Asia and the Western Pacific. While Indonesia itself is known as a country with a very high level of consumption and production of tobacco products, even occupying the top three positions in the world. In this study, researchers aim to give an idea, what kind of dilemma faced and what are the influential factors in it. Not only domestic dilemmas but dilemmas at the international level related to the existence of WHO as a world health organization. With the theory of cooperation dilemma as the main foundation and human security as a supporting concept. The research method used is qualitatively descriptive. Obtained from interview/correspondence data, literature studies, and other documents related to Indonesia's dilemma against WHO-FCTC. Based on the results of the study, it shows that Indonesia is indeed experiencing a dilemma on two sides. Dilemmas on the internal side include problems in the economic and health fields, while in the external sphere cooperative relations with WHO are at stake. This dilemma is an important point in decision making carried out by Indonesia. Although it does bring up the posibility of other problems